Stability of Two Probiotics Bacteria of Goat Milk Yoghurt in Rat Digestive Tract - RARAH RATIH ADJIE MAHESWARI; I KOMANG GEDE WIRYAWAN; GINA LESMANA MADUNINGSIH (Microbiology Indonesia, 2008)
Increased age will affect the bacterial population of the human digestive tract, in which many bacteria will adapt and colonize different sites. Combining probiotics and prebiotics in what has been called a synbiotic could beneficially affect the host by improving survival and implantation/adhesion of live microbial dietary supplements in the gastrointestinal flora. Probiotic bacteria are expected to survive in the digestive tract to give health effects to the host by balancing the intestinal microflora. The addition of fructo-oligosaccharides is expected to increase viability and growth of probiotics in the digestive tract. The objective of the current research is to investigate the effect of probiotic yoghurt and synbiotic yoghurt of Etawa Breed Cross Saanen (PESA) goats together with fructo-oligosaccharides, on female rats and to study the stability of probiotic bacteria in the digestive tracts. The results showed that synbiotic yoghurt intake had no significant influence (p>0.05) on ration consumption, body weight gain, feed conversion, final body weight and mortality. The synbiotic intake significantly increased the population of Bifidobacterium longum (p